Interferometric measurements of many-body topological invariants using mobile impurities - F. Grusdt (Nature Portfolio, 2016)
Probing topological orders in many-body systems remains a major challenge, which requires bulk-edge correspondence. Here, Grusdt et al.present an approach to show that fractional charges can be directly probed in the bulk of fractional quantum Hall systems using mobile impurities through interferometric measurements.